2004
DOI: 10.1016/s0002-9440(10)63114-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Elastolytic Cysteine Proteases, Cathepsins S and K, in the Neointima of Balloon-Injured Rat Carotid Arteries

Abstract: The matrix-degrading activity of several proteases are involved in the accelerated breakdown of extracellular matrix associated with vascular remodeling during the development of atherosclerosis and vascular injury-induced neointimal formation. Previous studies have shown that the potent elastolytic cysteine proteases, cathepsins S and K, are overexpressed in atherosclerotic lesions in human and animal models. However, the role of these cathepsins in vascular remodeling remains unclear. In the present study, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 37 publications
5
85
0
5
Order By: Relevance
“…45 Another possible explanation is that attenuation of the inflammatory response by AP caused reduced vein wall injury, or AP inhibited other matrix enzymes such as cathepsins or serum elastase. 46 The latter contribution may be most important, and is a subject of future study.…”
Section: Discussionmentioning
confidence: 98%
“…45 Another possible explanation is that attenuation of the inflammatory response by AP caused reduced vein wall injury, or AP inhibited other matrix enzymes such as cathepsins or serum elastase. 46 The latter contribution may be most important, and is a subject of future study.…”
Section: Discussionmentioning
confidence: 98%
“…Cat S exhibits pronounced elastolytic and collagenolytic activities in vitro and in vivo [21] . Cheng et al [11] showed that Cat S is expressed at only a low level in the LV myocardium of control rats or normal humans.…”
Section: Discussionmentioning
confidence: 99%
“…Focus has been given to the elastolytic activities of cathepsins S and K. Both cathepsins are potent elastin-degrading proteases surpassing the in vitro activities of prototype elastases such as pancreatic, leukocyte, and metalloelastases (MMP-12). The expression of cathepsins S and K has been described in smooth muscle cells and macrophages, with both cell types being critical in the pathophysiology of the arterial vascular system (3,45). Elastin is an integral component of the intima and responsible for the elasticity of the blood vessels.…”
Section: Discussionmentioning
confidence: 99%